Factors Affecting Employee Performance: A Quantitative Study: Faktor-faktor yang Mempengaruhi Kinerja Karyawan: Studi Kuantitatif - Erlina Rahmawati; Hasan Ubaidillah (Academia Open, 2024)
This study aimed to examine the influence of work discipline, work ethos, and work environment on employee performance using a quantitative method. The study collected data from 169 production employees using a questionnaire and analyzed the data using SPSS 22. The results showed that work discipline, work ethos, and work environment have a significant impact on employee performance, and these factors have a simultaneous effect on employee performance. The study's implication is that companies should prioritize work discipline, work ethos, and work environment to improve employee performance. The study adds to the growing body of research on the importance of these factors in enhancing employee performance. Highlight: The study used a quantitative method to examine the impact of work discipline, work ethos, and work environment on employee performance. The study collected data from 169 production employees using a questionnaire and analyzed the data using SPSS 22. The results showed that work discipline, work ethos, and work environment have a significant impact on employee performance, and these factors have a simultaneous effect on employee performance. The study's implication is that companies should prioritize work discipline, work ethos, and work environment to improve employee performance. Keywords: work discipline, work ethos, work environment, employee performance, quantitative method